Land day, a reminder of what is at stake in Palestine - Guediri, Kaoutar (Dar Al Safir, 2019)
42 years apart, both Land Day in Israel and the Great March in Gaza were protests against the very fundamentals of Zionist settler-colonialism or any settler-colonialism for that end as they focused on both dimensions, land and population.